TI_GERICHTE 16.2005.82 vom 25. August 2005 , stralcio per ritiro esecuzione - desistenza uguale soccombenza - TI Tribunale d'appello (2005)
stralcio per ritiro esecuzione - desistenza uguale soccombenza